The first record of Baccharis L. (Asteraceae) as a host-plant genus for Nepticulidae (Lepidoptera), with description of new Stigmella species from South America - Stonis, Jonas R.; Diškus, Arūnas; Remeikis, Andrius; Remeikis, Andrius; Davis, Donald R.; Solis, M. Alma; Torres, Nixon Cumbicus (Zootaxa, 2016)
We record the first Nepticulidae species found to feed on Baccharis L. (Asteraceae). Despite the high species richness of Baccharis in the Western Hemisphere, no nepticulid has ever been recorded feeding on Baccharis. In this paper we describe six new Stigmella Schrank species feeding on Baccharis: S. emarginatae Diškus & Stonis, sp. nov., S. bipartita Diškus & Stonis, sp. nov., S. tripartita Diškus & Stonis, sp. nov., S. latifoliae Remeikis, Diškus & Stonis, sp. nov., S. baccharicola Diškus & Stonis, sp. nov., and S. confertae Diškus & Stonis, sp. nov. The remaining two taxa are left unnamed. All taxa are illustrated with photographs of adults, their genitalia, and their leaf-mines. Additionally, leaf-mines on Baccharis salicifolia are documented.